Then ’Ogham Stones’: sources for the study of ‘Hibernia’ and ‘Britannia romana’ (and post-Roman Britain) - Santos, Dominique (Romanitas - Revista de Estudos Grecolatinos, 2016)
Since the establishment of History as a Science (Geschichtswissenschaft), among the major transformations of historiographical field one can notice the expansion of the notion of document, no longer understood only as written texts but as any evidence of human presence. Like other areas, Ancient History also followed these changes, which led into a renewal of sources, materials and methods for the study of Antiquity. This article aims at presenting some notes about a documentary corpus little explored by Brazilian historiography, the Ogham Stones, important material evidence for the study of Hibernia and Britannia romana (and post-Roman Britain).